Circular economy transition barriers in the construction and demolition sector - Majed Alzara; Ahmed Abd Elnasser; Mohammed Abdelshakor; Ahmed Ehab (PLoS ONE, 2025)
This study evaluates the readiness of Egypt’s construction sector to integrate Circular Economy (CE) principles by identifying and analyzing the main barriers to effective Construction and Demolition Waste (CDW) management. A comprehensive survey-based methodology (n = 384) was employed to gather data from industry stakeholders, demonstrating excellent sampling adequacy (KMO = 0.961). Initially, 41 potential barriers were identified via literature review and expert consultation. Exploratory Factor Analysis (EFA) subsequently refined these to 10 critical barriers, whose interrelationships were validated using Structural Equation Modeling (SEM), exhibiting a strong model fit (RMSEA = 0.065; CFI = 0.974). The analysis revealed persistent economic, technological, and social barriers impeding CE adoption. Notable challenges include high implementation costs, inadequate technical expertise, low stakeholder awareness, and weak policy enforcement. Based on these findings, prioritized, time-phased recommendations are proposed to provide an evidence-based framework for policy and practice. This research contributes an early empirical assessment of CE adoption in Egypt’s construction sector, offering a robust roadmap for a more sustainable, resource-efficient industry aligned with national environmental and economic objectives.